Influence of ergometer design on physiological responses during rowing - Rossi, J.; Piponnier, E.; Vincent, L.; Samozino, P.; Messonnier, L. (International Journal of Sports Medicine, 2015)
The aim of this study was to compare the physiological responses and rowing efficiency on 2 different rowing ergometers: stationary vs. dynamic ergometers manufactured by Concept2. 11 oarswomen and oarsmen rowed 4?min at 60% and 70% of peak power output on both ergometers (randomized order). Power output, stroke rate, heart rate, oxygen uptake, carbon dioxide production, lactate accumulation and rating of perceived exertion were recorded at each stage on the 2 ergometers. Gross and net efficiencies were computed. Exercise intensity was associated with increases in all parameters. Rowing on dynamic ergometer was associated with higher heart rate, oxygen uptake, carbon dioxide production and stroke rate, concomitantly to lower blood lactate accumulation but also to lower gross and net efficiencies. The present study showed that rowing efficiency and blood lactate accumulation were lower on the Concept2 dynamic ergometer than on its stationary counterpart. If the use of the Concept2 dynamic ergometer may provide some advantages (reduced risk of injuries), its utilization requires a specific evaluation of physiological responses during an incremental exercise for an adapted management of training.